Theoretical Study Of Legal Protection Of Song Royalty On Digital Platforms - Sahrul Sahrul; Yogabakti Adipradana Setiawan; Wahyu Wahyu (Jurnal Ilmiah Dunia Hukum, 2023)
The purpose of this study is to solve problems related to legal arrangements regarding song royalties or music on digital platforms that are used commercially and the issue of violations of song royalties on digital platforms today. This type of research is normative legal research with primary legal materials covering the applicable laws and regulations and secondary legal materials, including law books, the internet, and journals related to the issues studied. This research is descriptive, while the research material is carried out qualitatively. This research results in a conclusion that the matter of collecting royalties for songs on the Digital Platform after the issuance of Government Regulation of the Republic of Indonesia Number 56 of 2021 concerning Management of Royalties for Copyright of Songs and/or Music only targets the form of public services but does not regulate strictly in the form of Digital services that are used commercially and Legal protection regarding royalties for songs or music in Digital Platforms that are used commercially is divided into 2 (two), namely: Legal protection in the form of protection of works and rights for songwriters in the form of economic rights and moral rights, legal protection in the form of criminal sanctions and civil sanctions in the form of compensation. The responsibility of Government must immediately make derivative regulations relating to the Management of Song Royalties in Digital Platforms that are used commercially to provide protection and legal certainty for those who have economic rights/song royalties, as well as the Directorate General of Intellectual Property (DJKI) to be able to complete the Song / Music Information System (SILM) song and music data center to optimize the withdrawal and distribution of royalties to songwriters or musicians.